If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 5u = -16 Solving -6 + 5u = -16 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5u = -16 + 6 Combine like terms: -6 + 6 = 0 0 + 5u = -16 + 6 5u = -16 + 6 Combine like terms: -16 + 6 = -10 5u = -10 Divide each side by '5'. u = -2 Simplifying u = -2
| 5+2n-2=7n+9-3n | | 3/p=7/9 | | -v+25=166 | | 36(2)= | | 114=155-v | | 3x+2x=-13 | | 166=-x+282 | | 0.06+0.03(100-x)=1.2 | | 7/3+4y=8y-1/15 | | 5[2x-7]=2 | | 5[2x-7]=2 | | 5.9+7.3x=11.5x | | 5(3x+4)=4(6x-4) | | 2(3b-4)=2(n+3) | | -x+169=281 | | 3/8=24c | | 4a-5+2a+9=21 | | 9-3x+12=15 | | 3(x+4)=6(x-10) | | 51=y+7 | | 264-x=182 | | 6+12n-5=5n+46-2n | | y=4x^2+25x-21 | | 1.2x+-4y=28 | | 3x+4=10x-6 | | 18/x-4=10/x | | X/7+1=-1 | | 1/3x+y=6 | | X-a+4=ax+2b-6 | | 1/2(4a+10)=2+ | | 9=5x-4x+5 | | 4ab+9=c |